Common trends and common cycles in Canada: who knew so much has been going on? - Elizabeth C. Wakerly; Byron G. Scott; James M. Nason (Federal Reserve Bank of Atlanta, 2004)
It is generally accepted that convergence is well established for regional Canadian per capita outputs. The authors present evidence that long-run movements are driven by two stochastic common trends in this time series. This evidence casts doubt on the convergence hypothesis for Canada. Another prevalent belief is that Canada forms an optimal currency area (OCA). The authors uncover three serially correlated common cycles whose asymmetries suggest Canada is not an OCA. Their common trend-common cycle decomposition of regional outputs also reveals that trend shocks dominate fluctuations in Ontario, Quebec, and the Maritimes in the short run and long run but not in British Columbia and the Prairie region. Thus, regional Canadian economic fluctuations are driven by a rich, diverse, and economically important set of propagation and growth mechanisms.
Keywords: 330